2021
DOI: 10.2196/26111
|View full text |Cite
|
Sign up to set email alerts
|

With Great Hopes Come Great Expectations: Access and Adoption Issues Associated With COVID-19 Vaccines

Abstract: Although COVID-19 vaccines are becoming increasingly available, their ability to effectively control and contain the spread of the COVID-19 pandemic is highly contingent on an array of factors. This paper discusses how limitations to vaccine accessibility, issues associated with vaccine side effects, concerns regarding vaccine efficacy, along with the persistent prevalence of vaccine hesitancy among the public, including health care professionals, might impact the potential of COVID-19 vaccines to curb the pan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Consistent with our findings, survey studies found that safety and efficacy were among the most common COVID-19 vaccine concerns reported by the public and health care workers [ 37 - 40 ]. Additionally, studies have identified safety concerns as being one of the most common reasons for COVID-19 vaccine hesitancy [ 8 , 38 - 42 ]. In the United States, surveys indicate that 10% to 20% of adults and an estimated 8% of health care workers will refuse COVID-19 vaccines [ 8 , 37 , 39 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings, survey studies found that safety and efficacy were among the most common COVID-19 vaccine concerns reported by the public and health care workers [ 37 - 40 ]. Additionally, studies have identified safety concerns as being one of the most common reasons for COVID-19 vaccine hesitancy [ 8 , 38 - 42 ]. In the United States, surveys indicate that 10% to 20% of adults and an estimated 8% of health care workers will refuse COVID-19 vaccines [ 8 , 37 , 39 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in alignment with Google's current intentions, we recommend that all COVID-19 vaccine FAQs be linked to government and academic answer sources; this would provide people with transparent and quality vaccine information. At a minimum, FAQs on safety and efficacy should be answered by government sources, as safety and efficacy concerns are among the primary drivers of COVID-19 vaccine hesitancy [39][40][41][42].…”
Section: Recommendationsmentioning
confidence: 99%
“…The urgency to vaccinate young adults and foster healthy vaccination habits in this population is particularly pronounced in light of the rising negative media surrounding vaccination, as seen amid the COVID-19 pandemic ( Su et al., 2020b , Su et al., 2020c , Su et al., 2021b , Su et al., 2021a , Su et al., 2021c , Szabo, 2021 ) ( Szabo, 2021 ). Both fact-based (e.g., legitimate reports on side effects) and fake news powered (e.g., vaccine conspiracy theories), which could not only compromise both the effectiveness of vaccination promotion campaigns but also people’s vaccination intentions ( Mason and Donnelly, 2000 ; Rosselli et al., 2017 ; Nyhan et al., 2014 ; Meyer et al., 2016 ; Su et al., 2020b , Su et al., 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…Though successful COVID-19 vaccination campaigns are contingent on many factors ranging from effective vaccine communication, vaccine efficacy, vaccine distribution, vaccine administration, to equitable vaccine accessibility [9][10][11], among all these factors, vaccine accessibility is perhaps the most important contributor upon which the rest of the components depend. For instance, debates about which vaccine is more efficacious or easier to transport are meaningless unless people have access to actual COVID-19 shots so that they can test their efficacy or transport them between places.…”
Section: The Humanitarian Imperative Of Vaccine Empathymentioning
confidence: 99%